THE EFFECTIVENESS OF WHATSAPP GROUPS AS A COMMUNICATION MEDIA IN THE DIVISION OF WORK AT PT. SATUNADA - Sari Putri Rizki; Priatna (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to analyze the utilization of WhatsApp as an organizational communication medium for work distribution at PT. Satunada. WhatsApp was chosen due to its practical features, cost efficiency, and accessibility to all employee levels. This research employed a descriptive qualitative approach through in-depth interviews with key informants, including the manager, administrative staff, and field operators at PT. Satunada. The findings revealed that WhatsApp plays a significant role in accelerating information delivery, facilitating cross-division coordination, and supporting real-time documentation of work distribution. The group feature in WhatsApp enables all team members to receive messages simultaneously, thereby reducing the risk of miscommunication and enhancing transparency in task assignments. Nevertheless, the study identified challenges such as potential disruption of employees’ rest time due to messages sent outside working hours, as well as the blending of personal and work-related messages. Therefore, it is recommended that the company establish clear and structured digital communication policies to optimize WhatsApp usage without creating additional psychological burdens for employees.